The Effect of Strategic Collaboration Approach on the National Educational Standards Achievement and Service Quality in Basic Education at Local Government in Indonesia - Mashuri H Tahili; Ismail Tolla; Mohammad Arifin Ahmad; Abdul Saman; Sulaiman Samad (Research in Social Sciences and Technology- OpenED Network, 2021)
This study measures the effect of strategic collaboration approach on the Educational National Standards (ENS) and the basic education service quality at local government in Indonesia The research used a quantitative method. We used 489 teachers and 271 school principals in primary and secondary schools. The data were collected through questionnaires for the quantitative data and analyze using a structural model. The research findings confirm strategic collaboration approach has a positive and significant effect on ENS and basic education service quality. Further, the educational national standards have a positive and significant effect on the basic education service. In this study, we found that the strategic collaboration approach may employ in basic education to perform basic education performance. We argue that to better implementation of strategic collaboration approach, the greater improvement of the achievement of ENS and basic education service quality at local government in Indonesia.